Impact of biological education and gender on students’ connection to nature and relational values - Kleespies, Matthias Winfried; Dierkes, Paul Wilhelm (PLOS ONE, 2020)
The new concept of relational values (RVs) is gaining more and more attention in environmental research, but empirical analyses are still rare. However, this type of research is necessary because the RVs have an influence on environmental behavior. To evaluate the impact of biological education on attributing higher importance to RVs and connectedness to nature, we compared the connection to nature scores (using the inclusion of nature scale (INS) and connectedness to nature scale (CNS)) and RV scores of biologically interested high school students (n = 417) with first year (n = 593) and advanced biology (n = 223) students. While high school students showed significant lower connection to nature scores than university students, there was no significant difference in RVs between the test groups. These results suggest that there is a lack of factors in the university study of biology that can change RVs. The gender comparison of RVs and connection to nature showed a significant higher RV score for females while INS and CNS did not show a gender difference. Thus, the study makes an important contribution to the research, as it was able to prove that gender has an influence on a person's RVs but not on their connection to nature.